2021
DOI: 10.1016/j.ijid.2021.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of P.1 variant of SARS-CoV-2 in a cluster of cases in Salvador, Brazil

Abstract: We report three cases of severe COVID-19 due to the SARS-CoV-2 P.1 lineage in a familial cluster detected in Salvador, Bahia-Brazil. All cases were linked to travel by family members from the state of Amazonas to Bahia in late December 2020. This report indicates the cryptic transmission of the SARS-CoV-2 P.1 lineage across Brazil and highlights the importance of genomic surveillance to track the emergence of new SARS-CoV-2 variants of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Our findings showed that the P.1 lineage was present in Southern Brazil soon after, in late November. Later, other early detections of the P.1 lineage were described in other Brazilian States, such as Bahia, Salvador city 19 .…”
Section: Discussionmentioning
confidence: 86%
“…Our findings showed that the P.1 lineage was present in Southern Brazil soon after, in late November. Later, other early detections of the P.1 lineage were described in other Brazilian States, such as Bahia, Salvador city 19 .…”
Section: Discussionmentioning
confidence: 86%
“…The P.1 variant from Brazil includes 11 substitutions in S protein: L18F, T20N, P26S, D138Y, R190S, K417T, E484K, N501Y, D614G, H655Y, T1027I [ 81 , 82 ]. In vitro studies have shown that BNT162b2 elicited sera equally neutralized wild-type and a recombinant SARS-CoV-2 expressing an S protein with P.1 variant mutations, indicating an unlikely viral escape from vaccination [ 83 ].…”
Section: Efficacy Of Vaccines Against the New Sars-cov-2 Variantsmentioning
confidence: 99%
“…This N501Y mutation is associated with the highest transmissibility and has given rise to other lineages with additional mutations in the S-protein RBD ( 35 ). The emergence of a triple-mutated variant (K417T, E484K, N501Y, B.1.1.28), referred to as Gamma SARS-CoV-2, has been reported in Brazil ( 36 , 37 , 38 , 39 ). The Gamma variant has shown high transmissible rates, inherent immune escape from neutralizing antibodies ( 40 , 41 , 42 ), and increased propensity of reinfection.…”
Section: Introductionmentioning
confidence: 99%